صور التعاون الدولي في مكافحة الجريمة المنظمة - مروة بن يحي; خديجة لشقر (My University, 2024)
Abstract The technological advancements across various fields have enhanced the ability of organized crime to easily traverse borders, posing significant challenges for law enforcement and judicial authorities. This is due to the evolving nature of criminal patterns and their utilization of sophisticated technological and artistic methods in executing their criminal schemes, making detection more difficult. Thus, it necessitates the unified efforts and cooperation among nations to address this issue. International cooperation contributes to promoting international peace and security, as well as achieving justice and protecting the rights and freedoms of individuals. Additionally, it aids in strengthening international relations and fulfilling the goals of the international community by enhancing international cooperation through the conclusion of international agreements and bilateral and multilateral treaties, particularly in legal and judicial domains. Moreover, it involves establishing organizations and bodies, whether at the international or regional levels, with regards to the security field. ............................ ملخص المذكرة عزز التطور التكنولوجي الحاصل في مختلف المجالات من قدرة الجريمة المنظمة على الانتقال بسهولة عبر الدول، الأمر الذي جعلها تشكل تحديا كبيرا للسلطات الأمنية والقضائية وذلك نظرا لتعدد وتجدد أنماطها واستخدامها لوسائل تقنية وفنية متطورة في تنفيذ مخططاتها الإجرامية مما أدى إلى صعوبة الكشف عنها، وهو ما يستدعي توحيد جهود الدول والتعاون فيما بينها لمحاولة التصدي لهذه الجريمة. حيث يساهم التعاون الدولي في تعزيز السلم والأمن الدوليين، بالإضافة إلى تحقيق العدالة وحماية حقوق وحريات الأفراد كما يساعد على تقوية العلاقات الدولية، ويحقق المجتمع الدولي أهدافه في تعزيز التعاون الدولي من خلال إبرام الاتفاقيات الدولي ومعاهدات الثنائية والمتعددة الأطراف هذا بالنسبة إلى المجالين القانوني والقضائي، وإنشاء المنظمات والهيئات سواء على المستوى الدولي أو الإقليمي بالنسبة للمجال الأمني. ......................... Résumé Le développement technologique dans divers domaines a renforcé la capacité de la criminalité organisée à se déplacer facilement à travers les frontières, ce qui en fait un défi majeur pour les autorités de sécurité et judiciaires. La diversité et le renouvellement constant de ses modes opératoires, ainsi que l'utilisation de moyens techniques et artistiques sophistiqués pour exécuter ses plans criminels, rendent sa détection difficile. Cela nécessite une unification des efforts des pays et une coopération entre eux pour tenter de lutter contre cette criminalité. La coopération internationale contribue à renforcer la paix et la sécurité internationales, ainsi qu'à réaliser la justice et à protéger les droits et libertés des individus. Elle aide également à renforcer les relations internationales. La communauté internationale atteint ses objectifs de promotion de la coopération internationale par la conclusion d'accords et de traités internationaux bilatéraux et multilatéraux dans les domaines juridique et judiciaire, et par la création d'organisations et d'institutions au niveau international ou régional dans le domaine de la sécurité.